‘Ilm al-Așwat (Phonetic and Phonology) Naẓariyātuhā wa Taṭawwurātihā wa Ahdāfu Tadrīsihā - Rizka Widyanti (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2017)
AbstractPhonology is one of the most important linguistic sciences, which consists of phonetics and phonology. The phonetics is a science that studies the sounds physically and organically in terms of their production, exits, pronouns and descriptions, while the phonology is a science that studies sounds functionally within specific language structures in terms of their properties, characteristics and its function semantically. Thus, we know and we can distinguish the pronunciation device and its members to describe the strange sounds, and so on. This science have maintained to focus on sounds from the beginning of its publication that the fact it is the language of speech which used by people for their interaction. This article aims to elaborate the sounds described in terms of the type of the outcomes and its theories from the past and contemporary where there is disagreement among their statement scientifically. On the other side, this article try to elaborate upon issues in phonology such as the development in tones and intonations, especially in Arabic language.Keywords: Phonology, Phonetics, Tones, Intonation, Meanings. علم الأصوات (الفوناتيك والفونولوجيا)نظرياتها وتطوراتها وأهداف تدرسيها بقلم: رزقا ويدايـانتيالمعهد العـالي الإسلامي دار القرآن باياكمبوه سومطرا الغربية(uni_qoen@yahoo.com) ملخصيعد علم الأصوات من أهم العلوم اللغوية حيث يتكون على الفوناتيك والفونولوجيا. والفوناتيك هو علم يدرس الأصوات فيزيائيا وعضويا من حيث إنتاجها ومخارجها وأعضاء نطقها وصفاتها. كما أن الفونولوجيا هو علم يدرس الأصوات وظيفيا داخل تراكيب لغة معينة من حيث خصائصها وصفاتها ووظيفتها الدلالية. منهما نعرف ونستطيع أن نفرق جهاز النطق وعضاؤه، ووصف الأصوات العريبة وغير ذلك. وقد يركز هذا العلوم على الأصوات من بداية إصدارها إلى كونها لغة الكلام اتصل بها الناس بعضها بععض. وتتحدث هذه المقالة العليمة على الأصوات وصفها من ناحية مخارج الحروف وأنواعها ونظريتها عند القدماء والمحتدثين حيث يكون من بينهم الخلاف في نظر هذا العلم. وتتحدث في جانب أخر على القضايــا في علم الأصوات مثل النبر والتنغيم وغيرها ثم تطورتها. وفي نهاية، تقدم بعض الأهداف الخاصة في تعليم الأصوات العربية.الكلمة الرئيسية: علم الأصوات، الفوناتيك، الفونولوجيا، النبر، التــــــنغيــم، المعانى